Effectiveness Of Nalbuphine As An Adjuvant To Ropivacaine In Ultrasound Guided Supraclavicular Brachial Plexus Block - A Randomised Control Study - S, Pavana; Patel Hs, Prajwal; Tn, Chethanananda; R, Raghavendra (Journal of Neonatal Surgery, 2025)
Introduction: Supraclavicular brachial plexus block (SCBPB) provides excellent anaesthesia for upper limb surgeries. Ropivacaine is commonly used due to its favourable safety profile, but its single-shot effect may not suffice for prolonged postoperative analgesia. Nalbuphine, a mixed κ-agonist and µ-antagonist opioid, is a promising adjuvant with effective analgesia and minimal side effects. This study aims to evaluate the effect of adding nalbuphine (10 mg) to 0.75% ropivacaine in ultrasound-guided supraclavicular brachial plexus block. Materials and Methods: This randomised controlled study included 60 patients undergoing upper limb surgeries, divided into two groups (n=30). Group A received 20 mL of 0.75% ropivacaine with 10 mg nalbuphine; Group B received 20 mL of 0.75% ropivacaine with 1 mL normal saline. Ultrasound-guided SCBPB was performed, and onset and duration of sensory and motor block, duration of analgesia, and hemodynamic parameters were assessed. Results: Group A demonstrated significantly faster sensory (3.9 ± 1.2 vs 9.0 ± 1.8 min) and motor block onset (7.1 ± 1.4 vs 11.8 ± 2.0 min) compared to Group B (p < 0.001). Duration of motor block (810 ± 45 vs 665 ± 40 min) and analgesia (1020 ± 60 vs 801 ± 50 min) were significantly longer in Group A (p < 0.001). Hemodynamic and respiratory parameters remained stable in both groups, and no adverse effects were reported. Conclusion: Nalbuphine (10 mg) significantly improves the onset and duration of sensory and motor blockade, as well as postoperative analgesia, when used as an adjuvant to ropivacaine in SCBPB, without compromising safety.